On New Year's Eve - Zocchi, Judith Mazzeo; Wallis, Rebecca (Sea Girt, N.J. : Dingles & Co, 2005)
Describes the ways many Americans greet the new year, including parties and New Year's resolutions, and also includes facts on new year celebrations around the world and a craft activity.
3.7
3-6.
3-6
Keywords: Holidays -- Juvenile literature; New Year -- Juvenile literature; Holidays; New Year; Holidays; New Year